Grinding process monitoring based on electromechanical impedance measurements - Marchi, Marcelo [UNESP]; Baptista, Fabricio Guimaraes; Aguiar, Paulo Roberto de; Bianchi, Eduardo Carlos [UNESP] (Iop Publishing Ltd, 2015)
Grinding is considered one of the last processes in precision parts manufacturing, which makes it indispensable to have a reliable monitoring system to evaluate workpiece surface integrity. This paper proposes the use of the electromechanical impedance (EMI) method to monitor the surface grinding operation in real time, particularly the surface integrity of the ground workpiece. The EMI method stands out for its simplicity and for using low-cost components such as PZT (lead zirconate titanate) piezoelectric transducers. In order to assess the feasibility of applying the EMI method to the grinding process, experimental tests were performed on a surface grinder using a CBN grinding wheel and a SAE 1020 steel workpiece, with PZT transducers mounted on the workpiece and its holder. During the grinding process, the electrical impedance of the transducers was measured and damage indices conventionally used in the EMI method were calculated and compared with workpiece wear, indicating the surface condition of the workpiece. The experimental results indicate that the EMI method can be an efficient and cost-effective alternative for monitoring precision workpieces during the surface grinding process.
Keywords: Grinding; Monitoring; Electromechanical impedance; Piezoelectric transducers